Anatomische preparaten van kinabasten in de simpliciacollectie van het Universiteitsmuseum Utrecht - Lambers, Paul (Studium, 2019)
In the historic pharmacognostic collection of the University Museum Utrecht, originally from the pharmaceutical department of the university, are two sets of in total 150 microscopic slides (a series of 125 and a distinct series of 25 slides) of bark of species of Cinchona. These pertain to two publications on the anatomy of the bark of Cinchona trees by the pharmacist and botanist prof. Phillip Phoebus from Giessen, respectively from 1864 and 1867. The two series are the only left of six similar couples that were sent by Phoebus in 1864 and 1866 to the Dutch Ministry of Colonies, to be distributed among universities and kina researchers in the Netherlands and the Dutch East-Indies. Together with an extensive mail correspondence between the ministry, Phoebus, and the main Dutch Cinchona researchers, kept in the archive of the Ministry of Colonies in the National Archive, this small collection illustrates an important phase in Cinchona research and politics in the second half of the 19th century.